Treating inflammation and infection in the 21st century: new hints from decoding resolution mediators and mechanisms - Serhan, Charles N (The FASEB journal, 2017)
Practitioners of ancient societies from the time of Hippocrates and earlier recognized and treated the signs of inflammation, heat, redness, swelling, and pain with agents that block or inhibit proinflammatory chemical mediators. More selective drugs are available today, but this therapeutic concept has not changed. Because the acute inflammatory response is host protective to contain foreign invaders, much of today's pharmacopeia can cause serious unwanted side effects, such as immune suppression. Uncontrolled inflammation is now considered pathophysiologic and is associated with many widely occurring diseases such as cardiovascular disease, neurodegenerative diseases, diabetes, obesity, and asthma, as well as classic inflammatory diseases ( , arthritis and periodontal diseases). The inflammatory response, when self-limited, produces a superfamily of chemical mediators that stimulate resolution of the response. Specialized proresolving mediators (SPMs), identified in recent years, are endogenous mediators that include the n-3-derived families resolvins, protectins, and maresins, as well as arachidonic acid-derived (n-6) lipoxins, which promote resolution of inflammation, clearance of microbes, reduction of pain, and promotion of tissue regeneration novel mechanisms. Aspirin and statins have a positive impact on these resolution pathways, producing epimeric forms of specific SPMs, whereas other drugs can disrupt timely resolution. In this article, evidence from recent human and preclinical animal studies is reviewed, indicating that SPMs are physiologic mediators and pharmacologic agonists that stimulate resolution of inflammation and infection. The findings suggest that it is time to challenge current treatment practices-namely, using inhibitors and antagonists alone-and to develop immunoresolvents as agonists to test resolution pharmacology and their role in catabasis for their therapeutic potential.-Serhan, C. N. Treating inflammation and infection in the 21st century: new hints from decoding resolution mediators and mechanisms.